VD_FINDINFO Jug / 2018 / 81 vom 26. Oktober 2017 - VD Tribunal cantonal (2017)
DROIT PÉNAL DES MINEURS, SURSIS À L'EXÉCUTION DE LA PEINE, FIXATION DE LA PEINE | 47 CP, 35 DPMin, 398 al. 3 let. b CPP (CH)